Motivation Behind E-Trust of Electronic banking Channels by Banks - Dornklaimz Enamhe; Chidiebere U. Enukoha; Pius U. Angioha; Manderson Kusi (ARRUS Journal of Engineering and Technology, 2021)
This quantitative study attempts to validate the adoption of electronic banking channels by commercial banks for operational performance. The study was a survey that adopted a structured self-designed questionnaire to elicit data from management staff selected from commercial banks in Cross River states using proportional and simple random sampling techniques. Descriptive statistics and Pearson Product Moment correlation was used to analyse the collected data. Electronic banking channels were measured by automated teller machines and internet banking to analyse the data, and this was measured continuously. Analyse results validates the adoption of electronic banking channels (Automated teller machines and Internet banking). The study suggests factors that improve digital banking for bank profitability and operational performance based on these findings